2018
DOI: 10.1002/ima.22303
|View full text |Cite
|
Sign up to set email alerts
|

Optical positioning technology of an assisted puncture robot based on binocular vision

Abstract: Percutaneous image‐guided interventions are increasing in number in clinical practice because they are minimally invasive. Needle positioning placement is crucial and highly dependent on the physician's skills and experience, it is often the longest part of the intervention. Medical robotics and computer‐assisted surgery are hotspots in the field of robotics and medicine, changing the essence of traditional surgery using a combination of robotic, image processing, and computer technologies. The present paper a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Jiang et al aimed to study a robot-assisted puncture procedure based on optical positioning technology. This robot can be used for point marking in puncture operations [ 4 ]. Zhang et al proposed an exploration on restriction innovation in light of recurrence regulation band computerized sound telecom (FM-CDR) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al aimed to study a robot-assisted puncture procedure based on optical positioning technology. This robot can be used for point marking in puncture operations [ 4 ]. Zhang et al proposed an exploration on restriction innovation in light of recurrence regulation band computerized sound telecom (FM-CDR) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 8 shows the actual pose information of the object in the scene in the robot base coordinate system can be read from the robot teaching device, and the robot can be manually operated to move its end to the designated position for recording. The rotation angle of the target around any of the x, y, and z axes is around 180° [25][26][27]. Therefore, the error between the pose of the object obtained by the program matching and the actual pose of the object in the scene is shown in the figure: 1 shows that through the statistics and analysis of the pose error results of the target object, the average error on the x, y and z axes is 4.12mm, 3.56mm and 3.87mm respectively, and the overall average position error is 3.85mm.…”
Section: Random Sorting Experiments Of Target Objectsmentioning
confidence: 99%
“…As shown in Figure 8, in order to further illustrate that the improved DTW algorithm has better recognition rate and accuracy than other algorithms, the k-NN algorithm and the decision tree algorithm are used in the experiment to classify these five sets of actions. Recognition, it can be found that the DTW recognition algorithm recognizes five types of table tennis batting action recognition rate are higher than k-NN algorithm, and decision tree recognition algorithm [31][32][33][34][35].…”
Section: Recognition Of Batting Actionmentioning
confidence: 99%